2007
DOI: 10.1097/01.jcn.0000287030.95370.d0
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Dyspnea and Blood Pressure in Chronic Obstructive Pulmonary Disease

Abstract: The first 4 periods following use of the incentive spirometer were found to have statistically significant increases from dyspnea baseline scores (F = 77.4, P < .001). The baseline of each of the arterial blood pressure measurements, systolic, mean, and diastolic, were found to have significant differences with all of the 6 postintervention time points (systolic F = 8.0, P < .001; mean F = 7.1, P < .001; diastolic F = 7.2, P < .001). The changes in dyspnea scores and blood pressure measurements were found to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…COPD patients show a high prevalence of cardiovascular disease, higher than expected given their age and the coexistence of classic cardiovascular risk factors [8]. Several studies have demonstrated associations between COPD and abnormalities of systemic vascular dysfunction [9,10]. This is a very complex interaction.…”
Section: Discussionmentioning
confidence: 99%
“…COPD patients show a high prevalence of cardiovascular disease, higher than expected given their age and the coexistence of classic cardiovascular risk factors [8]. Several studies have demonstrated associations between COPD and abnormalities of systemic vascular dysfunction [9,10]. This is a very complex interaction.…”
Section: Discussionmentioning
confidence: 99%